Coach-athlete relationships: A qualitative study of professional sport teams in Australia - Bennie, A.; O'Connor, D. (International Journal of Sport & Health Science, 2012)
This paper examines perceptions of effective coaching and coach-athlete relationships within professional team sports in Australia. The findings are based on interviews with six male professional coaches and 25 players from cricket, rugby league, and rugby union. Qualitative data analysis reveals that relationships within professional sport settings are based on mutual respect, trust and honesty. The results also indicate that professional coaches and players describe two different types of coach-athlete relationships-the close, `family` oriented relationship or the `professional`, arms-length relationship-both of which are considered equally effective as long as the coaches and athletes share the same attitude towards the relationship. These findings have implications for effective coaching and how coaches interact to develop relationships with their athletes. They demonstrate that if coaches are to be perceived as effective, it is crucial to consider individual athlete preferences with respect to the type of relationship formed. This highlights the need for specialised coach training in people management as the professional coaching role increasingly requires attention to personal development in conjunction with the technical, tactical and physical training of their athletes.